Strategi Efektif dalam Komunikasi untuk Meningkatkan Pelayanan Perpustakaan - Intan Nikfatul Awaliyah (IJAL (Indonesian Journal of Academic Librarianship), 2024)
Strategy is a way or method for planning over a long period of time which is expected to achieve certain goals and principles. In communication, strategies are also needed to achieve communication goals. Libraries in improving their usability need to update the methods used to attract user attention. Changes are made either through changing regulations, adding programs and services, or improving communication strategies with users. One communication tool is social media. Including Surya at SDMT, the strategy used in the SDMT library is using an approach to students or users, guidance in the e-library, working with guardian teachers, the Surya SDMT Ponorogo library also provides a display of new books which are available on the school notice board and provide good information directly or indirectly, which aims to create communication so that it can improve the quality that occurs in the library.